Assessing cost-effectiveness with equity of a programme targeting marginalised girls in secondary schools in Tanzania. Issue 1 (2nd January 2021) - Sabates, Ricardo; Rose, Pauline; Alcott, Benjamin; Delprato, Marcos
ABSTRACT: Cost-effectiveness studies rarely pay explicit attention to whether resources are used effectively to benefit the most marginalised. By linking a quasi-experimental design with detailed financial information, we analyse the cost-effectiveness of the Campaign for Female Education (CAMFED)'s programme in Tanzania. The programme provides targeted, multi-dimensional support to marginalised girls in government secondary schools in deprived rural areas. We find the cost-effectiveness of CAMFED's programme to be similar to interventions designed for more advantaged populations who are easier (and less costly) to reach. There is further evidence of positive spill-over effects to boys in the schools supported by CAMFED.